Seleção de microrganismos de solo contaminados com cobre e seu potencial como bioagente - Debastiani, Giovana Lara (My University, 2024)
The climatic conditions of the southern region of Brazil favor the appearance of plant diseases, requiring the application of fungicides, where the most commonly used are copperbased. Due to the long period of use, soils contaminated by excess of this element are already a reality, especially in vine cultivation, the principal and oldest crop in Serra Gaúcha. Therefore, this work aimed to identify the diversity of prokaryotic communities associated with vineyard soils with a high concentration of copper, subsequently isolating and selecting microorganisms with potential promotion of plant growth and control of phytopathogens through antagonism. The experiments were conducted in the Laboratory of Biological Control of Plant Diseases at the University of Caxias do Sul and Microbiology and Molecular Biology at the University of Vale do Taquari. A total of three soil samples were collected from viticultural soils contaminated by excess copper, named old organic (VO), old conventional (VC), and new conventional (NC), where part of the soil was intended for identification of the microbial genus using sequencing of the 16S region of rRNA. Part of it was characterized through chemical analysis. Regarding microbial genetic diversity, 35 phyla were identified, where the most representative, with 15.24% of total sample dissimilarity, was attributed to the phylum Proteobacteria, with approximately 40% representation. The phyla most affected by Copper contamination were Rokubacteria, Bacteroidetes, Verrucomicrobia, and Latescibacteria. Bacterial isolation resulted in 14 isolates, which produced Indolic Compounds (IC), with strains S20 and S26 being the biggest producers and can also produce siderophores, emphasizing strains S19 and S26. The bacteria Bacillus sp. S26, isolated from VO soil, showed more significant potential in the in vitro antagonism test with the phytopathogens Fusarium venenatum, Botryosphaeria dothidea, and Botrytis cinerea and the bacteria Bacillus sp. S26 inhibited the growth of all three, the most significant being observed in the control of Botrytis cinerea. The in vitro antagonistic activity against Colletotrichum spp. identified some bacterial strains that inhibited the growth of phytopathogens, the bacterial strain being Bacillus sp. S26 chosen for the antagonism experiment in grape berries inoculated with Colletotrichum acutatum, presenting a 3.5-fold reduction in incidence in the preventive treatment and also in inoculation in vine plants propagated by cutting and micropropagation methods, wherein the first gave greater weight dryness of the aerial part and in the second helped in the resistance of plants in Cu-contaminated soils, but when the plants grew without stress, no growth-promoting effect was identified. These data showed that Bacillus sp. S26 has the potential for the development of an inoculant bioproduct that reduces the symptoms of biotic and abiotic stresses in grapevines. [resumo fornecido pelo autor]
A cultura da videira, que é o principal e mais antigo cultivo da Serra Gaúcha está sob condições climáticas que favorecem o aparecimento de doenças de plantas, sendo necessária a aplicação de fungicidas. Os mais utilizados, nos vinhedos, são a base de cobre e em função do longo tempo de aplicações, solos contaminados por excesso deste elemento já são uma realidade no Sul do Brasil, Desta forma, o objetivo deste trabalho foi identificar a diversidade das comunidades procarióticas associadas a solos de vinhedos com alta concentração de cobre, posteriormente isolar e selecionar microrganismos com potencial promoção de crescimento vegetal e controle de fitopatógenos por antagonismo. Os experimentos foram realizados nos Laboratórios de Controle Biológico de Doenças em Plantas da Universidade de Caxias do Sul e de Microbiologia e Biologia Molecular da Universidade do Vale do Taquari. Um total de três amostras de solo foram coletadas de solos vitícolas contaminados por excesso de cobre, nomeados velho orgânico (VO), velho convencional (VC) e novo convencional (NC). Parte do solo foi destinado para identificação do gênero microbiano utilizando o seqüenciamento da região 16S do rRNA e parte foi caracterizado através de análise química. Em termos de diversidade genética microbiana foram identificados 35 filos, onde o mais representativo com 15,24% de dissimilaridade total das amostras foi atribuído ao filo Proteobacteria, com aproximadamente 40% de representatividade. Os filos mais afetados pela contaminação por Cobre foram Rokubacteria, Bacteroidetes, Verrucomicrobia e Latescibacteria. O isolamento bacteriano resultou em 14 isolados, que produziram Compostos Indólicos (IC), destacando-se como os maiores produtores as linhagens S20 e S26 e também podem produzir sideróforos, com ênfase para as cepas S19 e S26. Isolada do solo VO, a bactéria Bacillus sp. S26, in vitro, apresentou maior potencial no teste de antagonismo com os fitopatógenos Fusarium venenatum, Botryosphaeria dothidea e Botrytis cinerea a bactéria Bacillus sp. S26 inibiu o crescimento dos três, sendo que o mais expressivo foi observado no controle do Botrytis cinerea. A atividade antagonista in vitro contra Colletotrichum spp. identificou algumas cepas bacterianas que inibiram o crescimento dos fitopatógenos, sendo a cepa bacteriana Bacillus sp. S26 escolhida para o experimento de antagonismo em bagas de uva inoculadas com Colletotrichum acutatum, apresentando no tratamento preventivo redução de 3,5 vezes na incidência e também de inoculação em plantas de videira propagadas pelos métodos de estaquia e micropropagação. O primeiro método apresentou maior peso seco da parte aérea e no segundo auxilou na resistência das plantas em solos contaminados com Cu, mas quando as plantas cresceram sem estresse, nenhum efeito de promoção de crescimento foi identificado. Esses dados mostraram que o Bacillus sp. S26 apresenta potencial para o desenvolvimento de um bioproduto inoculante redutor dos sintomas de estresses bióticos e abióticos na videira. [resumo fornecido pelo autor]
Keywords: Antibiose; Bacillus subtilis; Biotecnologia; Videira; Cobre; Antibiosis; Biotechnology; Vine; Copper